MODELING OF POWER SYSTEMS AND TESTING OF RELAY PROTECTION DEVICES IN REAL AND MODEL TIME - I. V. Novash (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The methods of modelling of power system modes and of testing of relay protection devices with the aid the simulation complexes in real time and with the help of computer software systems that enables the simulation of virtual time scale are considered. Information input protection signals in the simulation of the virtual model time are being obtained in the computational experiment, whereas the tests of protective devices are carried out with the help of hardware and software test systems with the use of estimated input signals. Study of power system stability when modes of generating and consuming electrical equipment and conditions of devices of relay protection are being changed requires testing with the use of digital simulators in a mode of a closed loop. Herewith feedbacks between a model of the power system operating in a real time and external devices or their models must be determined (modelled). Modelling in real time and the analysis of international experience in the use of digital simulation power systems for real-time simulation (RTDS simulator) have been fulfilled. Examples are given of the use of RTDS systems by foreign energy companies to test relay protection systems and control, to test the equipment and devices of automatic control, analysis of cyber security and evaluation of the operation of energy systems under different scenarios of occurrence of emergency situations. Some quantitative data on the distribution of RTDS in different countries and Russia are presented. It is noted that the leading energy universities of Russia use the real-time simulation not only to solve scientific and technical problems, but also to conduct training and laboratory classes on modelling of electric networks and anti-emergency automatic equipment with the students. In order to check serviceability of devices of relay protection without taking into account the reaction of the power system tests can be performed in an open loop mode with the use of hardware and software test systems. Testing methods for relay protection and their models in open-loop mode have been proposed.